EFFECT OF ANTENATAL COUNSELLING ON EXCLUSIVE BREASTFEEDING - Ahmad, Muhammad Owais; Sughra, Ume; Kalsoom, Umay; Imran, Muhammad; Hadi, Usman (Journal of Ayub Medical College Abbottabad, 2012)
Background: The promotion and support of breastfeeding is a global priority. However, in reality most of the mothers are unable to practice exclusive breastfeeding. Most mothers discontinue breastfeeding because of lack of confidence in their ability to breastfeed, problem with infant suckling, breast pain, perception of insufficient milk, in addition to other unspecified difficulties. Some these problems can be solved if the women are counselled antenataly about the benefits of breastfeeding and prepared mentally for exclusive breastfeeding. The aim of the study was to determine whether the mothers with antenatal counselling on breastfeeding would improve their exclusive breast feeding and compare this with that of the mothers without antenatal counselling. It was a cross-sectional comparative study which took place at the Maternity ward of Fauji Foundation Hospital, Rawalpindi. Methods: Hundred mothers selected by consecutive non probability sampling divided in two groups. Group A: 50 mothers who were counselled on breastfeeding and Group B: 50 mothers who were not counselled on breastfeeding. Fifty mothers practicing breast feeding after antenatal counselling in the maternity ward of Fauji Foundation Hospital, Rawalpindi were recruited in the study. Another fifty mothers practicing breastfeeding without antenatal counselling were asked to take part in the study as a control group. Performa was completed and an informed consent was obtained. Results: As compared to the not counselled group, the mothers who initiated breastfeeding immediately after birth were statistically significantly higher (p<0.046) in the counselled group (84% and 96% respectively). Similarly the number of counselled mothers who practiced exclusive breastfeeding was statistically very highly significantly more (p<0.001) than the not counselled group (68% and 16% respectively). Conclusion: Antenatal counselling helps in motivating the mothers for initiation of breastfeeding immediately after birth and practicing exclusive breastfeeding for first six months of infant’s life. Existing antenatal counselling on breastfeeding is inadequate in the population studied and needs to be strengthened. Keywords: Breastfeeding, Antenatal counselling, Exclusive breastfeeding